ANALISIS FAKTOR-FAKTOR PENYEBAB LAMBATNYA PERSETUJUAN KPR (KREDIT PEMILIKAN RUMAH) DI BANK TABUNGAN NEGARA KC MAGELANG - Saputra, Rheno Arya; Musthafa, Afif (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
Home Ownership Credit (KPR) is one of the financing facilities that is highly sought after by the public in an effort to meet housing needs. As one of the banks focused on housing financing, Bank Tabungan Negara (BTN) plays an important role in distributing KPR, including at the Magelang Branch Office. However, in its implementation, the mortgage approval process does not always run smoothly. Various obstacles often arise, such as incomplete documentation and the financial condition of the debtor not meeting the requirements. These obstacles can slow down credit approval and impact customer satisfaction. Understanding the factors that cause these delays is an important step in improving the effectiveness of KPR services at BTN KC Magelang.